Sulphonated cellulose-based carbon as a green heterogeneous catalyst for biodiesel production: process optimization and kinetic studies - Saikia, Kankana; Ngaosuwan, Kanokwan; Assabumrungrat, Suttichai; Singh, Bhaskar; Okoye, Patrick U.; Rashid, Umer; Rokhum, Samuel Lalthazuala (Elsevier, 2023)
We report, the catalytic application of sulphonated cellulose based solid carbon catalyst for conversion of oleic acid to methyl oleate-biodiesel production under microwave irradiation. Oleic acid, being one of the most widely found fatty acids in plant oils and animal fats; it was utilized as a model substrate to produce biodiesel in this study. The effect and interaction of four independent factors such as methanol to oleic acid molar ratio (MOMR), time, catalyst loading, and temperature were investigated using response surface methodology (RSM). After doing the thirty experiments given by the central composite design (CCD), the optimized reaction condition using RSM was found to be MOMR of 21:1, 60 min, 8 wt % catalyst loading, and temperature of 80 ◦C that predicted 96.77% biodiesel yield under microwave irradiation, whereas, 97.6 ± 0.2% yield was observed experimentally. The kinetic study of the esterification reaction showed that it followed a pseudo first order reaction. The activation energy of the esterification was found to be relatively low at 49.19 kJ mol− 1 . The catalyst showed good recyclability when explored up to the 5th reaction cycle. The SEM analysis of the recycled catalyst showed its stability for at least 5 reaction cycles. Therefore, it can be promoted for sustainable production of biodiesel due to its moderate preparation method, good catalytic efficiency, and excellent recyclability.